Resistant starch—An accessible fiber ingredient acceptable to the Western palate. Issue 3 (27th April 2022) - Walsh, Sarah Kate; Lucey, Alice; Walter, Jens; Zannini, Emanuele; Arendt, Elke K.
Abstract: Dietary fiber intakes in Western societies are concerningly low and do not reflect global recommended dietary fiber intakes for chronic disease prevention. Resistant starch (RS) is a fermentable dietary fiber that has attracted research interest. As an isolated ingredient, its fine particle size, relatively bland flavor, and white appearance may offer an appealing fiber source to the Western palate, accustomed to highly refined, processed grains. This review aims to provide a comprehensive insight into the current knowledge (classification, production methods, and characterization methods), health benefits, applications, and acceptability of RS. It further discusses the present market for commercially available RS ingredients and products containing ingredients high in RS. The literature currently highlights beneficial effects for dietary RS supplementation with respect to glucose metabolism, satiety, blood lipid profiles, and colonic health. An exploration of the market for commercial RS ingredients indicates a diverse range of products (from isolated RS2, RS3, and RS4) with numerous potential applications as partial or whole substitutes for traditional flour sources. They may increase the nutritional profile of a food product (e.g., by increasing the fiber content and lowering energy values) without significantly compromising its sensory and functional properties. Incorporating RS ingredients into staple food products (such as bread, pasta, and sweet baked goods) may thus offer an array of nutritional benefits to the consumer and a highly accessible functional ingredient to be greater exploited by the food industry.